Mitochondrial Fission Is Required for Angiotensin II-Induced Cardiomyocyte Apoptosis Mediated by a Sirt1-p53 Signaling Pathway - Qi, Jia; Wang, Feng; Yang, Ping; Wang, Xuelian; Xu, Renjie; Chen, Jihui; Yuan, Yanggang; Lu, Zhaoyang; Duan, Junli (Frontiers in Pharmacology, 2018)
Hypertension-induced cardiac apoptosis is a major contributor to early-stage heart-failure. Our previous studies have found that p53-mediated mitochondrial fission is involved in aldosterone-induced podocyte apoptosis. However, it is not clear that whether p53-induced mitochondrial fission is critical for hypertensive AngiotensinⅡ (AngⅡ)-induced cardiomyocyte apoptosis. In this study, we found that inhibition of the mitochondrial fission protein Drp1 (dynamin-related protein 1) by Mdivi-1 prevented cardiomyocyte apoptosis in SHR. In vitro we found that treatment of cultured neonatal rat cardiomyocytes with AngⅡinduced Drp1 expression, mitochondrial fission and apoptosis. Knockdown of Drp1 inhibited AngⅡ-induced mitochondrial fission and cardiomyocyte apoptosis. Furthermore, AngⅡinduced p53 acetylation. Knockdown of p53 inhibited AngⅡ-induced Drp1 expression, mitochondrial fission and cardiomyocyte apoptosis. Besides, we found that Sirt1 was able to reverse AngⅡ-induced p53 acetylation and its binding to the Drp1 promoter, which subsequently inhibited mitochondrial fission and eventually attenuated cardiomyocyte apoptosis. Collectively, these results suggest that AngⅡ degrades Sirt1 to increase p53 acetylation, which induces Drp1 expression and eventually results in cardiomyocyte apoptosis. Sirt1/p53/Drp1dependent mitochondrial fission may be a valuable therapeutic target for hypertension induced heart failure.